Institutional Direction as a Research Tool Methodological Foundations Market (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In the article the place and institutional changes in economy, it appears understanding of the institutional structure of the market, as a set of institutions and indicated the need for its reform. In addition, the authors determined approach to the chosen problem, outlines a range of outstanding issues related to institutional changes in the market. It turns out feature of the market as an institution designed model proposed market institutionalization. Outlines ways on institutional changes in market structure.
Keywords: market institute, institutional changes, neoinstytutsionalizm, postindustrialization, definition